The effect of speaker reliability on word learning in children: a replication study - Gangopadhyay, Ishanti; Peters, Lillian (Frontiers in Developmental Psychology, 2025)
This study aimed to replicate a previously conducted in-person speaker reliability experiment using a fully online methodology. Twenty children aged 4 to 6 years participated in a live video call with the experimenter and completed virtual tasks on a web-based platform. The experimental task mirrored that used in the previous reliability study, where children learned novel words from both a reliable and an unreliable speaker, followed by testing children's novel word retention. Consistent with the prior study's findings, children performed above chance in both conditions and retained novel labels taught by both speakers. These preliminary results suggest that speaker reliability is a robust cue, showing consistent effects across different data collection methods. Thus, online data collection shows promise for producing viable results and improving participation by making research more accessible and flexible. Nonetheless, further studies are necessary to explore its strengths and limitations, especially in the context of research involving children.